Self-perception of body image, nutritional status and practice of physical activity of university students from Rio Grande do Sul, Brazil - Bracht, Claudia Michele; da Rosa Piasetzki, Cláudia Thomé; Borin Busnello, Maristela; Moraes Berlezi, Evelise; Bento Franz, Ligia Beatriz; de Oliveira Boff, Eva Teresinha (O Mundo da Saúde, 2013)
The present study aimed to verify the perception of body self-image; nutritional status and practice of physical activity in undergraduate students in the area of health and education from a university of Rio Grande do Sul State. The sample consisted of 31 undergraduate students from the courses of Nutrition, Biology, Education and Physical Education, with a mean age of 23 years and 83.9% being female. The Body Shape Questionnaire was used to evaluate the perception of body image. In order to evaluate the level of physical activity, the International Physical Activity Questionnaire – IPAQ short version was used. The body mass index was calculated from weight and height. Arithmetic means, standard deviation, minimum and maximum values, and median, were calculated using the software Epi Info version 3.3.2. High levels of distortion in the perception of body image were observed among the pedagogy students (37.5%). The same was not observed among students of physical education and nutrition, that are courses in which, typically, students are more concerned with this situation. It was also observed that 50% of biology students had moderate body image distortion. In addition, the dissatisfaction with body image was more prevalent in women, and this was not related with socioeconomic status. Moreover, it was observed that physical activity and nutritional status were positively associated with body image perception. More researches should be conducted in order to elucidate a probable higher prevalence of eating and body image disorders among students.